2011
DOI: 10.1111/j.1749-6632.2010.05902.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of hypothalamic–pituitary–adrenal axis activity and function

Abstract: The hypothalamic-pituitary-adrenocortical (HPA) axis is a major neuroendocrine system involved in the regulation of numerous physiological processes and in adaptation to stress. A wide range of variability can be observed in all the components of the system, and the contribution of genetic factors has been shown in the central regulation of the axis, the production of glucocorticoid hormones by the adrenal cortex, their bioavailability, and the efficiency of their action at the level of receptor and postrecept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 107 publications
(199 reference statements)
3
38
0
Order By: Relevance
“…Several clinical studies have shown a relationship between CBG levels or CBG gene polymorphisms and metabolic parameters related to insulin resistance syndrome (e.g. Fernandez-Real et al, 2002;Barat et al, 2005;Richard et al, 2009), and the CBG locus has been shown to be linked with metabolic traits in several studies (see Moisan, 2010and Mormede et al, 2011aand 2011b for review), including in pigs (Desautes et al, 2002;Ousova et al, 2004), and we showed previously that CBG was a better predictor of carcass composition than cortisol levels (Ousova et al, 2004). In most cases, the physiological effects of CBG have been interpreted as resulting from the influence of CBG on the level and bioavailability of cortisol (Perogamvros et al, 2012;Moisan, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have shown a relationship between CBG levels or CBG gene polymorphisms and metabolic parameters related to insulin resistance syndrome (e.g. Fernandez-Real et al, 2002;Barat et al, 2005;Richard et al, 2009), and the CBG locus has been shown to be linked with metabolic traits in several studies (see Moisan, 2010and Mormede et al, 2011aand 2011b for review), including in pigs (Desautes et al, 2002;Ousova et al, 2004), and we showed previously that CBG was a better predictor of carcass composition than cortisol levels (Ousova et al, 2004). In most cases, the physiological effects of CBG have been interpreted as resulting from the influence of CBG on the level and bioavailability of cortisol (Perogamvros et al, 2012;Moisan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in adrenocortical axis activity may partly explain the compromised robustness that coincides with over-focused genetic improvement of production traits in farm animals. The large individual variation in HPA axis activity and reactivity, and the importance of genetic factors are well documented (Kadarmideen and Janss, 2007;Mormede et al, 2011a). We have therefore hypothesized that genetic selection for a more active HPA axis activity could improve robustness (Mormede et al, 2011b;Mormede and Terenina, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors are located in the cytoplasm, but on binding with a hormone, the receptors translocate into the nucleus and bind to hormone-responsive elements in the DNA, thus, increasing or decreasing the expression of a large number of genes in many tissues [7]. Cortisol results in metabolic effects stimulating hepatic gluconeogenesis, muscle tissue catabolism, and lipogenesis [4,8,9]. Furthermore, increased secretion of cortisol amplifies the mobilization of energy by lipolysis, glycogenolysis in the muscle, and gluconeogenesis induced by the catecholamines to supply the "fight or flight" response of the body to environmental challenges [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, during stress, these hormones are secreted at higher concentrations to promote adaptive coping. High concentrations of glucocorticoids affect metabolism, immune system, reproduction, inflammatory processes, and brain function [1][2][3][4]. The hypothalamic-pituitary-adrenal (HPA) axis releases pulses of adrenocorticotropic hormone (ACTH) into the circulation, which stimulates the cortex of the adrenal gland to produce and secrete cortisol, the major glucocorticoid.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the HPA response was shown to be deeply modulated by polymorphic variants of genes encoding the HPA axis components [19,20]. Indeed, we can hypothesize that HPA axis genetic polymorphisms may be also involved in controlling interpersonal variances in the coping capacity to prenatal stress.…”
Section: Introductionmentioning
confidence: 99%